Stereocontrolled Synthesis of Trichodermatide A1. Issue 13 (18th February 2013) - Shigehisa, Hiroki; Suwa, Yoshihiro; Furiya, Naho; Nakaya, Yuki; Fukushima, Minoru; Ichihashi, Yusuke; Hiroya, Kou
<x xml:space="preserve">Abstract</x> Hard core made easy: The pentacyclic core of trichodermatide A was stereoselectively synthesized from a bis(1, 3‐cyclohexanedione) derivative by a ring‐closing reaction followed by an intramolecular ketal formation (see scheme; PPTS=pyridinium p‐toluenesulfonate). The first total synthesis of trichodermatide A was then completed by the introduction of three hydroxy groups.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>